2018
DOI: 10.1039/c7tc04833e
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation of self-organization behavior in supramolecular π-conjugated polymer for multi-color electroluminescence

Abstract: Understanding the chain behavior and conformational/aggregation behavior of supramolecular π-conjugated polymer for multi-color electroluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…As self‐organization processes play a key role in the efficient production of highly ordered functional systems, they have been massively explored concerning the organic, inorganic, and organic–inorganic hybrid entities with molecular‐ and mesoscale periodicities . Among these, the self‐organizations of inorganics in polymers are of particular interest, which could lead to the construction of previously unknown functional materials with elaborate hybridized structures .…”
Section: Introductionmentioning
confidence: 99%
“…As self‐organization processes play a key role in the efficient production of highly ordered functional systems, they have been massively explored concerning the organic, inorganic, and organic–inorganic hybrid entities with molecular‐ and mesoscale periodicities . Among these, the self‐organizations of inorganics in polymers are of particular interest, which could lead to the construction of previously unknown functional materials with elaborate hybridized structures .…”
Section: Introductionmentioning
confidence: 99%
“…However, the R h was obviously increased to 89.0 nm with THF increased to 20%, while the R h was further increased up to 99.0 nm in 100% THF solvent (Figure b). From the correlation curve of dynamic light scattering (Figure a), it could be seen that when THF ratio increased gradually in the solution, PPFOH chains relaxation behavior slowed obviously, it indicated chain aggregation size became bigger gradually with THF ratio increase until cross-links or clusters structure was formed in a large-scale aggregation . From Figure b, it could be found that chain aggregate size presented rapid increase at first with THF ratio increase to 20%, and then increased slowly.…”
Section: Results and Discussionmentioning
confidence: 92%
“…This indicates that solvents in the PPFOH solution had less effect on condense state structure of the film after film-forming by spin coating. Reason was that the solvents could be volatilized in the process of solution to film due to low boiling point of CF 61 °C and THF 66 °C, strong intermolecular interaction between PPFOH molecules were formed in the process . But, in film from CF solvent, intermolecular interaction between PPFOH molecules was the strongest because of its lower boiling point than that of THF.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1–13 ] Specially relevant are those whose emission can be controlled with temperature, as luminescence can be detected remotely with highly sensitive and fast responsive techniques and offers time and spatial resolution at the macro‐ (e.g., luminescent labels) and nanoscale (e.g., fluorescence microscopy). Inherent thermofluorochromic materials involve thermoresponsive molecular dyes, [ 14–20 ] quantum dots, and lanthanide‐doped nanoparticles, [ 21 ] conjugated polymers, [ 22 ] or polymorphic dyes. [ 23 , 24,25 ] Even though several reports of the materials are available nowadays, their wide range of temperature responses and limited tunability of the color emission and/or switching temperature still hamper their complete implementation in commercial applications.…”
Section: Introductionmentioning
confidence: 99%